Analgetic and antiemetic action of the bilateral superficial cervical plexus blockade during thyroidectomy in patients with thyrotoxicosis - Тарасенко, Сергій Олександрович; Дубров, Сергій Олександрович; Ларін, Олександр Сергійович; Горобейко, Максим Борисович (ScienceRise: Medical Science, 2016)
Aim: the evaluation of antiemetic effect of bilateral blockage of superficial cervical plexus at the background of general anesthesia by sevoflurane or propofol in the complex of anesthesiology management of patients, who undergo thyroidectomy under conditions of specialized endocrinology center. Materials and methods. Patients are divided in 2 groups: the group of balanced analgesia (BA) -88 patients, control group 87 ones. Depending on the type of general anesthesia – inhalational by sevoflurane (S) or TIVA by propofol (P) patients were divided in subgroups BA –S-44 patients, BA-P – 44, C-S – 46 patients and C-P – 41 patients. In subgroups BA-S and BA-P was used the complex of balanced multimodal analgesia (BMMA) that included administration of dexamethasone, dekxketropofen and bilateral blockage of superficial cervical plexus (BBSCP) by 0,5 % solution of bupicavaine. The assessment of pain was carried out according to VAS, consumption of narcotic and non-narcotic analgetics, frequency and expressiveness of PONV during the first 24 hours of p/o period. Results and discussion. BMMA as BBSCP on the background of basic anesthesia by sevoflurane lowers the need and consumption of opioids, especially intraoperative consumption of fentanyl. Due to the high effectiveness of bilateral BSCP in subgroups of BA-S and BA-P it was not expedient to use the narcotic analgetics in p/o period as opposite to the groups C-S and C-P where they were used in 94,9 % and 93,7 % of patients respectively. According to VAS the pain in subgroups of BA-S and BA-P was weak and reliably (p<0,05) lower than in C-S and C-P. The use of BMMA on the background of basic anesthesia by sevoflurane in subgroup of BA-S provides intraoperative opioid-preserving action: the reliable (p<0,05) decrease of fentanyl consumption to 283,4±12,4 mcg for operation comparing with other subgroups. BMMA complex allowed reliably (p<0,05) raise the level of patients without PONV to 72,7 % and 77,3 % in subgroups of BA-S and BA-P respectively. The reliable decrease of the total sum of points according to PONV scale was attained in subgroup of BA-P to 0,36±0,11, that was by 60,6 % and 55,2 % less than in subgroups of C-S and C-P. For the subgroup of BA-S this index was 0,41±0,11 and was by 55,4 % and 49,4 % reliably (p<0,05) less than in subgroups of C-S and C-P. Conclusions. The best antiemetic system is the use of BMMA with BBSCP on the background of basic anesthesia by propofol with addition of metoplocramide before the induction of general anesthesia: the index of patients without PONV– 77,3 %, frequency of appearance of clinically significant PONV– 9,1 %, index of general sum of points according to PONV scale -0,36±0,11 (all indices are reliably less than in subgroups of C-S and C-P)